The Effect of Financial Literacy and Financial Education on Women's Healthy Financial Behavior through Investment Motivation - Sihar Tambun; Riris Rotua Sitorus; Fitri Nurwanti (University of Merdeka Malang, 2022)
This study aims to prove the effect of financial literacy and financial education on women's healthy financial behavior through investment motivation. The sample in this study consisted of 285 respondents from among women. Testing the data quality in this study uses Partial Least Square (PLS) analysis, namely the Structural Equation Modeling (SEM) equation model with a variance-based approach or component-based structural equation modeling. Based on the study results, financial literacy has a significant effect on women's healthy financial behavior through investment motivation, and financial education has a significant impact on women's healthy financial behavior through investment motivation. This study recommends to women, that if they want to create healthy financial behavior, then the priority strategy applied is to have excellent and adequate financial education, then try to have the motivation to invest in themselves and have good financial literacy. It is believed that the improvement of women's healthy financial behavior can help overcome the low percentage of women's literacy index in IndonesiaJEL: A2, G4, I2